A novel multilevel DC-link three-phase T-type inverter - Alnamer S.S.; Mekhilef S.; Mokhlis H.; Tan N.M.L. (MDPI AG, 2023)
Efficiency; Semiconductor diodes; Switching; Topology; Experimental validations; Fundamental frequencies; Low power application; Minimizing the number of; Modulation techniques; Multilevel converter; Switching transitions; Unequal DC-link voltages; Electric inverters